Artificial Intelligence: Prospects and Challenges in Future Progression - Mohajan, Haradhan Kumar (Art and Society, 2025)
Artificial intelligence (AI) is a branch of computer science that makes the computers to mimic the human behavior and assist humans for better performance in the field of science and technology. It refers to the ability of machines to perform cognitive tasks, such as thinking, perceiving, learning, problem solving, and decision making. The goal of it is to make a machine as smart as a human. Particular applications of AI are in advanced web search engines, internet, robotics, biometrics identification, speech recognition, natural language generation, virtual assistants, superhuman play, and to analysis in strategy games, autonomous vehicles, etc. At present many organizations are applying AI accurately and efficiently to provide security to their data and information systems. If AI system is not properly operated, it may face technical difficulties, data difficulties, security snags, etc. The purpose of this study is to discuss aspects of AI, and its present and future applications for the welfare of the global humanity.